High-strength fiber recycled concrete and preparation method thereof
Through triple modification treatment, the problems of rough surface and poor interface bonding force of recycled aggregates are solved, the mechanical properties and crack resistance of concrete are improved, and the recycling of resources and cost reduction are achieved.
Patent Information
- Application Number
- CN202411359889.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-27
AI Technical Summary
In practical applications, regenerated aggregates have rough surfaces, many pores, poor interfacial bonding force and strength limitations, which affect the mechanical properties of concrete.
Through triple modification treatment: calcium-containing ions promote liquid treatment, dopamine polymerization treatment and nanofiber modification, a dense calcium carbonate deposited layer, polydopamine film and nanofiber distribution are formed, and the density and mechanical properties of the aggregate surface are improved.
It significantly improves the surface strength and interface bonding force of recycled aggregates, improves the overall mechanical properties of concrete, enhances crack resistance, and realizes the recycling of resources, reducing the cost of concrete production.
Smart Images

Figure BDA0005064660720000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of recycled concrete, and more specifically relates to a high-strength fiber recycled concrete and a preparation method thereof. Background Art
[0002] With the acceleration of urbanization, the rapid development of the construction industry has generated a large amount of construction waste. Waste concrete, as a major type of construction waste, not only occupies a large amount of land resources, but also causes a certain degree of environmental pollution. How to effectively utilize these waste concrete and reduce its impact on the environment has become an urgent problem to be solved. In this context, the application of recycled aggregates has gradually received attention.
[0003] Recycled aggregate refers to a material that replaces natural aggregate after treating waste concrete through physical, chemical and other means. The application of recycled aggregate can effectively reduce the emission of construction waste, realize the recycling of resources, and thus reduce the cost of concrete production. However, compared with natural aggregate, recycled aggregate has some inherent defects and faces many challenges in practical application, mainly including: the surface of recycled aggregate is relatively rough and has more pores, resulting in poor interfacial adhesion between it and cement paste; the interface transition zone formed between recycled aggregate and cement paste is the weakest part of concrete and easily becomes the starting point for crack development; due to the strength limitation of recycled aggregate itself, the overall mechanical properties of concrete are affected.
[0004] In view of the above problems, how to provide a high-strength fiber recycled concrete and a preparation method thereof has become an issue that technical personnel in this field urgently need to overcome. Summary of the invention
[0005] The purpose of the present invention is to provide a high-strength fiber recycled concrete and a preparation method thereof to solve the problems existing in the above-mentioned prior art.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] One of the technical solutions of the present invention is to provide a high-strength fiber recycled concrete, which comprises, by weight:
[0008] 250-400 parts of cement, 800-1000 parts of modified recycled aggregate, 50-100 parts of fly ash, 2-6 parts of water reducer, 20-60 parts of steel fiber and 150-250 parts of water;
[0009] The modified recycled aggregate is prepared by sequentially being treated with a calcium ion-containing promoting liquid, polymerized with dopamine and modified with nanofibers.
[0010] Furthermore, the step of treating with the calcium ion-containing promoting liquid is:
[0011] The recycled aggregate is immersed in a calcium ion-containing promoting liquid, and then a carbonate solution is added to react for 30 to 60 minutes to complete the calcium ion-containing promoting liquid treatment.
[0012] Preferably, the calcium ion-containing promoting solution is a calcium acetate and / or calcium lactate solution, wherein the calcium ion concentration is 0.0125M to 0.125M.
[0013] Preferably, the carbonate in the carbonate solution is sodium carbonate and / or potassium carbonate, wherein the molar ratio of carbonate in the carbonate solution to calcium ions in the calcium ion-containing promoting solution is 0.9 to 1.1:1.
[0014] The present invention treats the regenerated aggregate with a calcium ion-containing promoting liquid and adds a carbonate solution to form a dense calcium carbonate deposition layer on the surface of the regenerated aggregate. This deposition layer can improve the density and strength of the aggregate surface, reduce water absorption, and improve the quality of the interface transition zone.
[0015] Furthermore, the step of the dopamine polymerization treatment is:
[0016] The recycled aggregate treated with the calcium ion-containing promoting liquid is immersed in a dopamine solution, and then the pH value of the dopamine solution is adjusted to above 8.5, reacted for 6 to 12 hours, and dried to complete the dopamine polymerization treatment.
[0017] Preferably, the concentration of the dopamine solution is 1 to 10 mg / mL.
[0018] Dopamine polymerization treatment forms a polydopamine (PDA) film on the surface of the recycled aggregate, further enhancing the interfacial adhesion between the aggregate and cement paste and giving the aggregate surface a certain self-healing ability.
[0019] Furthermore, the step of modifying the nanofibers is:
[0020] The recycled aggregate treated with dopamine polymerization is immersed in a nanofiber dispersion, left to stand for 12 to 24 hours, and then dried to obtain a modified recycled aggregate.
[0021] Preferably, the nanofiber dispersion is prepared by dispersing nanofibers and anionic surfactant in water.
[0022] More preferably, the mass percentage of nanofibers in the nanofiber dispersion is 0.01% to 0.1%, and the mass percentage of anionic surfactant is 0.1% to 1%.
[0023] More preferably, the nanofibers include carbon nanotubes, graphene or nanocellulose; and the anionic surfactant includes sodium dodecylbenzene sulfonate or sodium dodecyl sulfate.
[0024] The modification of nanofibers can further improve the mechanical properties of the aggregate surface and enhance its bonding with cement paste. At the same time, the uniform distribution of nanofibers on the aggregate surface can improve the overall mechanical properties of concrete.
[0025] Furthermore, the modified recycled aggregate consists of 60% to 80% by mass of coarse aggregate and 20% to 40% by mass of fine aggregate.
[0026] Among them, the grading range of coarse aggregate is 5-25mm, and the grading range of fine aggregate is <5mm.
[0027] Furthermore, the cement is silicate cement with a grade of PO42.5.
[0028] Furthermore, the water reducing agent is a polycarboxylic acid water reducing agent.
[0029] Furthermore, the steel fiber is a corrugated steel fiber or a hook-shaped steel fiber.
[0030] The second technical solution of the present invention is to provide a method for preparing the above-mentioned high-strength fiber recycled concrete, the steps comprising:
[0031] Mix the water reducer and water evenly to obtain mixing water;
[0032] The cement, the modified recycled aggregate, the fly ash and the steel fiber are uniformly mixed to obtain a dry mix;
[0033] The mixing water is added into the dry mixed material, and the mixture is stirred evenly to obtain the high-strength fiber recycled concrete.
[0034] The present invention discloses the following technical effects:
[0035] The present invention improves the performance of recycled aggregate through triple modification treatment, improves the density and strength of the recycled aggregate surface, reduces water absorption, improves the quality of the interface transition zone, enhances the interface adhesion between aggregate and cement paste, and gives the aggregate surface a certain self-repairing ability, improves the mechanical properties of the aggregate surface, and enhances its bonding with cement paste. At the same time, nanofibers are evenly distributed on the aggregate surface, thereby improving the overall mechanical properties of concrete.
[0036] The modified recycled aggregate has higher surface strength and better interface bonding force, which can reduce the weak links in the interface transition zone and cooperate with steel fibers to further improve the crack resistance of concrete.
[0037] The use of recycled aggregates from processed waste concrete reduces the emission of construction waste, achieves the recycling of resources, and reduces the cost of concrete production. DETAILED DESCRIPTION
[0038] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0039] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0040] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0041] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0042] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0043] The recycled aggregate used in the specific embodiment of the present invention is obtained by crushing waste concrete.
[0044] Other raw materials and reagents used in the specific embodiments of the present invention are commercially available products.
[0045] The modified recycled aggregate used in the specific embodiment of the present invention is composed of 70% by mass of coarse aggregate and 30% by mass of fine aggregate, wherein the gradation range of the coarse aggregate is 5-25 mm, and the gradation range of the fine aggregate is <5 mm.
[0046] The corrugated steel fiber or hook-shaped steel fiber used in the specific implementation scheme of the present invention has a length of 25 to 35 mm and a diameter of 0.3 to 0.5 mm, wherein the steel fiber with a length of 25 to 30 mm and a diameter of 0.3 to 0.4 mm accounts for 40 wt %; the steel fiber with a length of 30 to 35 mm and a diameter of 0.4 to 0.5 mm accounts for 60 wt %.
[0047] The fly ash used in the specific embodiment of the present invention is Class F Grade II fly ash that complies with GBT 1596-2017 "Fly ash for cement and concrete".
[0048] Example 1
[0049] The preparation steps of high-strength fiber recycled concrete are:
[0050] S1, immersing the recycled aggregate in a calcium ion promoting solution (calcium lactate, calcium ion concentration is 0.1M), then adding a carbonate solution (potassium carbonate, the molar ratio of carbonate concentration to calcium ion concentration is 1.1:1), reacting for 60 minutes, and drying to obtain recycled aggregate treated with the calcium ion promoting solution;
[0051] S2, immersing the regenerated aggregate treated with the calcium ion-containing promoting liquid obtained in step S1 in a dopamine solution (5 mg / mL), then adjusting the pH value to 8.5 with sodium hydroxide, reacting for 12 hours, and drying to obtain a regenerated aggregate treated with dopamine polymerization;
[0052] S3, immersing the recycled aggregate treated with dopamine polymerization in the nanofiber dispersion, standing for 24 hours, and then drying to obtain modified recycled aggregate;
[0053] The nano dispersion is prepared by dispersing nanofibers (carbon nanotubes) and anionic surfactants (sodium dodecylbenzene sulfonate) in water, wherein the mass percentage of nanofibers in the nanofiber dispersion is 0.05% and the mass percentage of anionic surfactants is 1%;
[0054] S4, raw material preparation: weigh 300 parts of cement (PO42.5), 900 parts of modified recycled aggregate in step S3, 80 parts of fly ash, 4 parts of polycarboxylic acid water reducer, 40 parts of corrugated steel fiber and 200 parts of water by mass, and set aside;
[0055] S5, uniformly mixing the polycarboxylate water reducer and water to obtain mixing water, and uniformly mixing cement, modified recycled aggregate, fly ash and corrugated steel fiber to obtain a dry mix;
[0056] S6. Add mixing water into the dry mix and mix evenly to obtain high-strength fiber recycled concrete.
[0057] Example 2
[0058] The preparation steps of high-strength fiber recycled concrete are:
[0059] S1, immersing the recycled aggregate in a calcium ion promoting solution (calcium acetate, calcium ion concentration is 0.125M), then adding a carbonate solution (sodium carbonate, the molar ratio of carbonate concentration to calcium ion concentration is 1:1), reacting for 50 minutes, and drying to obtain recycled aggregate treated with the calcium ion promoting solution;
[0060] S2, immersing the regenerated aggregate treated with the calcium ion-containing promoting liquid obtained in step S1 in a dopamine solution (10 mg / mL), then adjusting the pH value to 8.5 with sodium hydroxide, reacting for 12 hours, and drying to obtain a regenerated aggregate treated with dopamine polymerization;
[0061] S3, immersing the recycled aggregate treated with dopamine polymerization in the nanofiber dispersion, standing for 12 hours, and then drying to obtain modified recycled aggregate;
[0062] The nano dispersion is prepared by dispersing nanofibers (graphene) and anionic surfactant (sodium dodecyl sulfate) in water, wherein the mass percentage of nanofibers in the nanofiber dispersion is 0.1% and the mass percentage of anionic surfactant is 0.5%;
[0063] S4, raw material preparation: weigh 250 parts of cement (PO42.5), 800 parts of modified recycled aggregate in step S3, 50 parts of fly ash, 2 parts of polycarboxylic acid water reducer, 20 parts of hook-shaped steel fiber and 200 parts of water by mass, and set aside;
[0064] S5, uniformly mixing the polycarboxylate water reducer and water to obtain mixing water, and uniformly mixing cement, modified recycled aggregate, fly ash and hook-shaped steel fiber to obtain a dry mix;
[0065] S6. Add mixing water into the dry mix and mix evenly to obtain high-strength fiber recycled concrete.
[0066] Example 3
[0067] The preparation steps of high-strength fiber recycled concrete are:
[0068] S1, immersing the recycled aggregate in a calcium ion promoting solution (calcium acetate, calcium ion concentration is 0.0125M), then adding a carbonate solution (sodium carbonate, the molar ratio of carbonate concentration to calcium ion concentration is 0.9:1), reacting for 60 minutes, and drying to obtain recycled aggregate treated with the calcium ion promoting solution;
[0069] S2, immersing the regenerated aggregate treated with the calcium ion-containing promoting liquid obtained in step S1 in a dopamine solution (1 mg / mL), then adjusting the pH value to 8.5 with sodium hydroxide, reacting for 6 hours, and drying to obtain a regenerated aggregate treated with dopamine polymerization;
[0070] S3, immersing the recycled aggregate treated with dopamine polymerization in the nanofiber dispersion, standing for 12 hours, and then drying to obtain modified recycled aggregate;
[0071] The nano dispersion is prepared by dispersing nanofibers (nanocellulose) and anionic surfactant (sodium dodecylbenzene sulfonate) in water, wherein the mass percentage of nanofibers in the nanofiber dispersion is 0.01%, and the mass percentage of anionic surfactant is 0.1%;
[0072] S4, raw material preparation: weigh 400 parts of cement (PO42.5), 1000 parts of modified recycled aggregate in step S3, 100 parts of fly ash, 6 parts of polycarboxylic acid water reducer, 60 parts of corrugated steel fiber and 250 parts of water by mass, and set aside;
[0073] S5, uniformly mixing the polycarboxylate water reducer and water to obtain mixing water, and uniformly mixing cement, modified recycled aggregate, fly ash and corrugated steel fiber to obtain a dry mix;
[0074] S6. Add mixing water into the dry mix and mix evenly to obtain high-strength fiber recycled concrete.
[0075] Example 4
[0076] The preparation steps of high-strength fiber recycled concrete are:
[0077] S1, immersing the recycled aggregate in a calcium ion promoting solution (calcium lactate, calcium ion concentration is 0.125M), then adding a carbonate solution (sodium carbonate, the molar ratio of carbonate concentration to calcium ion concentration is 0.9:1), reacting for 30 to 60 minutes, and drying to obtain recycled aggregate treated with the calcium ion promoting solution;
[0078] S2, immersing the regenerated aggregate treated with the calcium ion-containing promoting liquid obtained in step S1 in a dopamine solution (10 mg / mL), then adjusting the pH value to 8.5 with sodium hydroxide, reacting for 6 hours, and drying to obtain a regenerated aggregate treated with dopamine polymerization;
[0079] S3, immersing the recycled aggregate treated with dopamine polymerization in the nanofiber dispersion, standing for 12 hours, and then drying to obtain modified recycled aggregate;
[0080] The nano dispersion is prepared by dispersing nanofibers (nanocellulose) and anionic surfactant (sodium dodecyl sulfate) in water, wherein the mass percentage of nanofibers in the nanofiber dispersion is 0.1%, and the mass percentage of anionic surfactant is 0.1%;
[0081] S4, raw material preparation: weigh 400 parts of cement (PO42.5), 800 parts of modified recycled aggregate in step S3, 100 parts of fly ash, 6 parts of polycarboxylic acid water reducer, 60 parts of hook-shaped steel fiber and 250 parts of water by mass, and set aside;
[0082] S5, uniformly mixing the polycarboxylate water reducer and water to obtain mixing water, and uniformly mixing cement, modified recycled aggregate, fly ash and hook-shaped steel fiber to obtain a dry mix;
[0083] S6. Add mixing water into the dry mix and mix evenly to obtain high-strength fiber recycled concrete.
[0084] Example 5
[0085] The preparation steps of high-strength fiber recycled concrete are:
[0086] S1, immersing the recycled aggregate in a calcium ion promoting solution (calcium acetate, calcium ion concentration of 0.0125M), then adding a carbonate solution (potassium carbonate, the molar ratio of carbonate concentration to calcium ion concentration is 1.1:1), reacting for 60 minutes, and drying to obtain recycled aggregate treated with the calcium ion promoting solution;
[0087] S2, immersing the regenerated aggregate treated with the calcium ion-containing promoting liquid obtained in step S1 in a dopamine solution (1 mg / mL), then adjusting the pH value to 8.5 with sodium hydroxide, reacting for 12 hours, and drying to obtain a regenerated aggregate treated with dopamine polymerization;
[0088] S3, immersing the recycled aggregate treated with dopamine polymerization in the nanofiber dispersion, standing for 12 hours, and then drying to obtain modified recycled aggregate;
[0089] The nano dispersion is prepared by dispersing nanofibers (graphene) and anionic surfactant (sodium dodecylbenzene sulfonate) in water, wherein the mass percentage of nanofibers in the nanofiber dispersion is 0.1% and the mass percentage of anionic surfactant is 1%;
[0090] S4, raw material preparation: weigh 400 parts of cement (PO42.5), 800 parts of modified recycled aggregate in step S3, 50 parts of fly ash, 4 parts of polycarboxylic acid water reducer, 30 parts of corrugated steel fiber and 250 parts of water by mass, and set aside;
[0091] S5, uniformly mixing the polycarboxylate water reducer and water to obtain mixing water, and uniformly mixing cement, modified recycled aggregate, fly ash and corrugated steel fiber to obtain a dry mix;
[0092] S6. Add mixing water into the dry mix and mix evenly to obtain high-strength fiber recycled concrete.
[0093] Comparative Example 1
[0094] The preparation steps of high-strength fiber recycled concrete are:
[0095] S1, immersing the recycled aggregate in a calcium ion promoting solution (calcium lactate, calcium ion concentration is 0.1M), then adding a carbonate solution (potassium carbonate, the molar ratio of carbonate concentration to calcium ion concentration is 1.1:1), reacting for 60 minutes, and drying to obtain recycled aggregate treated with the calcium ion promoting solution;
[0096] S2, immersing the regenerated aggregate treated with the calcium ion-containing promoting liquid obtained in step S1 in a dopamine solution (5 mg / mL), then adjusting the pH value to 8.5 with sodium hydroxide, reacting for 12 hours, and drying to obtain a modified regenerated aggregate;
[0097] S3, raw material preparation: weigh 300 parts of cement (PO42.5), 900 parts of modified recycled aggregate in step S2, 80 parts of fly ash, 4 parts of polycarboxylic acid water reducer, 40 parts of corrugated steel fiber, nanofiber (carbon nanotube) and 200 parts of water by mass, and set aside;
[0098] The amount of nanofibers used is the same as that used in step S3 of Example 1;
[0099] S4, mixing the polycarboxylate water reducer and water to obtain mixing water, and mixing cement, modified recycled aggregate, nanofiber (carbon nanotube), fly ash and corrugated steel fiber to obtain a dry mix;
[0100] S5. Add mixing water into the dry mix and mix evenly to obtain high-strength fiber recycled concrete.
[0101] Comparative Example 2
[0102] The preparation steps of high-strength fiber recycled concrete are:
[0103] S1. Immerse the recycled aggregate in a dopamine solution (5 mg / mL), then adjust the pH value to 8.5 using sodium hydroxide, react for 12 hours, and dry to obtain recycled aggregate treated with dopamine polymerization;
[0104] S2, immersing the recycled aggregate treated by dopamine polymerization in the nanofiber dispersion, standing for 24 hours, and then drying to obtain modified recycled aggregate;
[0105] The nano dispersion is prepared by dispersing nanofibers (carbon nanotubes) and anionic surfactants (sodium dodecylbenzene sulfonate) in water, wherein the mass percentage of nanofibers in the nanofiber dispersion is 0.05% and the mass percentage of anionic surfactants is 1%;
[0106] S3, raw material preparation: according to mass parts, weigh 300 parts of cement (PO42.5), 900 parts of modified recycled aggregate in step S2, 80 parts of fly ash, 4 parts of polycarboxylic acid water reducer, 40 parts of corrugated steel fiber and 200 parts of water, and set aside;
[0107] S4, mixing the polycarboxylate water reducer and water to obtain mixing water, and mixing cement, modified recycled aggregate, fly ash and corrugated steel fiber to obtain a dry mix;
[0108] S5. Add mixing water into the dry mix and mix evenly to obtain high-strength fiber recycled concrete.
[0109] Comparative Example 3
[0110] The preparation steps of high-strength fiber recycled concrete are:
[0111] S1, immersing the recycled aggregate in a calcium ion promoting solution (calcium lactate, calcium ion concentration is 0.1M), then adding a carbonate solution (potassium carbonate, the molar ratio of carbonate concentration to calcium ion concentration is 1.1:1), reacting for 60 minutes, and drying to obtain recycled aggregate treated with the calcium ion promoting solution;
[0112] S2, immersing the recycled aggregate treated with the calcium ion-containing promoting liquid in the nanofiber dispersion, standing for 24 hours, and then drying to obtain a modified recycled aggregate;
[0113] The nano dispersion is prepared by dispersing nanofibers (carbon nanotubes) and anionic surfactants (sodium dodecylbenzene sulfonate) in water, wherein the mass percentage of nanofibers in the nanofiber dispersion is 0.05% and the mass percentage of anionic surfactants is 1%;
[0114] S3, raw material preparation: according to mass parts, weigh 300 parts of cement (PO42.5), 900 parts of modified recycled aggregate in step S2, 80 parts of fly ash, 4 parts of polycarboxylic acid water reducer, 40 parts of corrugated steel fiber and 200 parts of water, and set aside;
[0115] S4, mixing the polycarboxylate water reducer and water to obtain mixing water, and mixing cement, modified recycled aggregate, fly ash and corrugated steel fiber to obtain a dry mix;
[0116] S5. Add mixing water into the dry mix and mix evenly to obtain high-strength fiber recycled concrete.
[0117] Comparative Example 4
[0118] The preparation steps of high-strength fiber recycled concrete are:
[0119] S1, immersing the recycled aggregate in a calcium ion promoting solution (calcium lactate, calcium ion concentration is 0.1M), then adding a carbonate solution (potassium carbonate, the molar ratio of carbonate concentration to calcium ion concentration is 1.1:1), reacting for 60 minutes, and drying to obtain recycled aggregate treated with the calcium ion promoting solution;
[0120] S2, immersing the regenerated aggregate treated with the calcium ion-containing promoting liquid obtained in step S1 in a dopamine solution (5 mg / mL), then adjusting the pH value to 8.5 with sodium hydroxide, reacting for 12 hours, and drying to obtain a modified regenerated aggregate;
[0121] S3, raw material preparation: according to mass parts, weigh 300 parts of cement (PO42.5), 900 parts of modified recycled aggregate in step S2, 80 parts of fly ash, 4 parts of polycarboxylic acid water reducer, 40 parts of corrugated steel fiber and 200 parts of water, and set aside;
[0122] S4, mixing the polycarboxylate water reducer and water to obtain mixing water, and mixing cement, modified recycled aggregate, fly ash and corrugated steel fiber to obtain a dry mix;
[0123] S5. Add mixing water into the dry mix and mix evenly to obtain high-strength fiber recycled concrete.
[0124] Comparative Example 5
[0125] Compared with Example 1, the only difference is that the concentration of the dopamine solution is 20 mg / mL.
[0126] Comparative Example 6
[0127] Compared with Example 1, the only difference is that the mass percentage of nanofibers in the nanofiber dispersion is 0.2%.
[0128] Comparative Example 7
[0129] Compared with Example 1, recycled aggregate without modification is used.
[0130] Test example
[0131] Test pieces of 150 mm×150 mm×500 mm were prepared by the methods of Examples 1 to 5 and Comparative Examples 1 to 7. After standard curing for 28 days, the cured test pieces were used as test samples for testing.
[0132] According to GB / T 50081-2016 “Standard for Test Methods for Mechanical Properties of Ordinary Concrete”, the compressive strength and splitting tensile strength of the test samples were tested, and the results are shown in Table 1.
[0133]
[0134] It can be seen from the data in Table 1 that the present invention shows higher compressive strength and splitting tensile strength due to the complete triple modification treatment, including calcium ion promoting liquid treatment, dopamine polymerization treatment and nanofiber modification. Compared with Example 1, Comparative Example 1 lacks the nanofiber modification step, and the nanofiber is directly added to the mixture as a filler, so the performance is slightly lower than that of Example 1; Comparative Example 2 lacks the calcium ion promoting liquid treatment step, resulting in a further decrease in its performance; Comparative Example 3 lacks the dopamine polymerization treatment step, resulting in a decrease in its performance; Comparative Example 4 lacks the nanofiber modification step, resulting in a slightly lower performance than the embodiment; Compared with Example 1, Comparative Example 5 has a higher concentration of dopamine solution, and a thicker polydopamine film is formed on the surface of the recycled aggregate, which affects the modification effect, so the performance is slightly reduced; Comparative Example 6 has a too high mass percentage of nanofibers, and the dispersibility in the dispersion is poor. Since the agglomeration affects the modification effect, the performance is similar to that of Comparative Example 1; In Comparative Example 7, the recycled aggregate has not undergone any modification treatment, so its performance is the worst.
[0135] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0136] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A high-strength fiber recycled concrete, characterized in that: By mass, the components include: 250-400 parts of cement, 800-1000 parts of modified recycled aggregate, 50-100 parts of fly ash, 2-6 parts of water reducer, 20-60 parts of steel fiber and 150-250 parts of water; The modified recycled aggregate is prepared by sequentially being treated with a calcium ion-containing promoting liquid, polymerized with dopamine and modified with nanofibers.
2. The high-strength fiber recycled concrete according to claim 1, characterized in that: The step of the calcium ion-containing promoting liquid treatment is: immersing the recycled aggregate in the calcium ion-containing promoting liquid, then adding a carbonate solution, reacting for 30 to 60 minutes, and completing the calcium ion-containing promoting liquid treatment.
3. The high-strength fiber recycled concrete according to claim 2, characterized in that: The calcium ion-promoting liquid is a calcium acetate and / or calcium lactate solution, wherein the calcium ion concentration is 0.0125M to 0.125M; the carbonate in the carbonate solution is sodium carbonate and / or potassium carbonate, wherein the molar ratio of carbonate in the carbonate solution to calcium ions in the calcium ion-promoting liquid is 0.9 to 1.1:
1.
4. The high-strength fiber recycled concrete according to claim 1, characterized in that: The steps of the dopamine polymerization treatment are: immersing the recycled aggregate treated with a calcium ion-containing promoting liquid in a dopamine solution, then adjusting the pH value of the dopamine solution to above 8.5, reacting for 6 to 12 hours, and drying to complete the dopamine polymerization treatment.
5. The high-strength fiber recycled concrete according to claim 4, characterized in that: The concentration of the dopamine solution is 1-10 mg / mL.
6. The high-strength fiber recycled concrete according to claim 1, characterized in that: The nanofiber modification step is: immersing the regenerated aggregate treated by dopamine polymerization in a nanofiber dispersion, standing for 12 to 24 hours, and drying to obtain modified regenerated aggregate.
7. The high-strength fiber recycled concrete according to claim 6, characterized in that: The nanofiber dispersion is prepared by dispersing nanofibers and anionic surfactants in water, wherein the mass percentage of nanofibers in the nanofiber dispersion is 0.01% to 0.1%, the mass percentage of anionic surfactants is 0.1% to 1%, the nanofibers include carbon nanotubes, graphene or nanocellulose, and the anionic surfactants include sodium dodecylbenzene sulfonate or sodium dodecyl sulfate.
8. The high-strength fiber recycled concrete according to claim 1, characterized in that: The modified recycled aggregate consists of 60% to 80% by mass of coarse aggregate and 20% to 40% by mass of fine aggregate; the cement is silicate cement with a grade of PO42.
5.
9. The high-strength fiber recycled concrete according to claim 1, characterized in that: The water reducer is a polycarboxylic acid water reducer; and the steel fiber is a corrugated steel fiber or a hook-shaped steel fiber.
10. A method for preparing high-strength fiber recycled concrete according to any one of claims 1 to 9, characterized in that the steps include: Mix the water reducer and water evenly to obtain mixing water; The cement, the modified recycled aggregate, the fly ash and the steel fiber are uniformly mixed to obtain a dry mix; The mixing water is added into the dry mixed material, and the mixture is stirred evenly to obtain the high-strength fiber recycled concrete.
Citation Information
Patent Citations
High-strength recycled aggregate concrete and preparation method thereof
CN115073097A
Concrete prepared by recycling waste concrete and preparation method thereof
CN115745447A
Green recycled aggregate reinforced concrete
CN116119984A
High-strength recycled concrete and preparation method thereof
CN116751004A
concrete
JP2004323294A
Cited By
Reinforcing process and application of recycled concrete fine aggregate
CN121107732A
